Very low enalapril and enalaprilat exposure via human milk: a case report from the ConcePTION project - Jacobs, Emily; Ceulemans, Michael; Nauwelaerts, Nina; de Nys, Siemon; Claes, Kathleen J.; Annaert, Pieter; Van Calsteren, Kristel; Smits, Anne; Allegaert, Karel; Van Neste, Martje (Frontiers in Pharmacology, 2026)
IntroductionOngoing maternal and clinical hesitancy in breastfeeding-related shared decision-making is driven by limited safety data on maternal pharmacotherapy. Theoretical exposure to maternal enalapril and its active metabolite enalaprilat in breastfed infants has previously been reported in two studies of eight mother-infant pairs. However, actual infant plasma concentrations remain uncharacterized.MethodsA 30-year-old white woman started enalapril (5 mg, 1x/day) for IgA nephropathy at 11 weeks postpartum while exclusively breastfeeding. On day 101 postpartum, 25 days after therapy start, she collected six steady-state milk samples over 24 h, along with two maternal and one infant blood sample, used to calculate milk-to-plasma (M/P) ratio and estimated infant exposure. Samples were analyzed using liquid chromatography with tandem mass spectrometry. Maternal and infant health information was concurrently collected via structured questionnaires.ResultsLow levels of enalapril (0.01–1.22 ng/mL) and enalaprilat (0.32–0.77 ng/mL) were measured in human milk. Using 200 and 150 mL/kg/day milk intake, estimated daily infant dosage was 78.32 ng/kg/day and 58.82 ng/kg for enalapril and 124.45 ng/kg/day and 93.34 ng/kg/day for enalaprilat, corresponding to a relative infant dose (RID) of 0.097% and 0.073% for enalapril. Infant enalapril and enalaprilat plasma concentrations were below the lower limit of quantification.DiscussionThese data support evidence of minimal transfer of enalapril and enalaprilat into human milk, suggesting low risk to breastfed infants, and may help address uncertainties in current clinical guidelines. This case report provides detailed maternal pharmacokinetic data for both compounds in human milk, alongside estimated infant exposure at 3 months postpartum.